1993
DOI: 10.1210/jcem.76.3.8445029
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 beta stimulates colony-stimulating factor-1 production in human term placenta.

Abstract: The human placenta produces hematopoietic growth factors including colony stimulating factor-1 (CSF-1). We have previously demonstrated Interleukin-1 beta (IL-1 beta) production by decidualized endometrium during pregnancy. Since IL-1 beta stimulates CSF-1 production in a variety of mesenchymal cell types including second trimester villous core mesenchymal cells, the present study was designed to determine if IL-1 beta could also regulate CSF-1 production in term placental explants in vitro. Placental villous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The plates were washed with PBST and then 1 pg/ml of sheep anti-rhSCF (Genzyme) was added and incubated for 1 hr at room temperature. Color development was performed using an avidin-biotin-peroxidase Vectastain kit (Vector Laboratories, Inc., Burlingame, CA) and 0-phenylenediamine dihydrochloride as the color substrate as previously described (Kauma, 1993). The plates were read at 490 nm in a V-max Kinetic Microplate Reader (Molecular Devices Corp., Palo Alto, CA).…”
Section: Elisa For Human Scfmentioning
confidence: 99%
“…The plates were washed with PBST and then 1 pg/ml of sheep anti-rhSCF (Genzyme) was added and incubated for 1 hr at room temperature. Color development was performed using an avidin-biotin-peroxidase Vectastain kit (Vector Laboratories, Inc., Burlingame, CA) and 0-phenylenediamine dihydrochloride as the color substrate as previously described (Kauma, 1993). The plates were read at 490 nm in a V-max Kinetic Microplate Reader (Molecular Devices Corp., Palo Alto, CA).…”
Section: Elisa For Human Scfmentioning
confidence: 99%
“…In humans, the placenta produces numerous hormones and growth factors, including human CG (hCG), human placental lactogen (hPL), progesterone (P4), estrogens (estradiol, estrone, estriol, and estetrol) (32,33), specific pregnancy j31 glycoprotein (SP1) (34), renin (35), human chorionic corticotropin (36), human chorionic TSH (37), human chorionic FSH, human uterotropic placental hormone (38), placental LH-releasing factor (39), TSHreleasing factor (40), somatostatin-like substance (41), human nerve growth factor (42), epidermal growth factor (EGF) (43), TGFs (43,44), and insulin-like growth factors (IGFs) (45). Recently, it was found that the placenta also produces cytokines such as interleukin-1 and interleukin-6, which stimulate hCG secretion in trophoblast cells (46)(47)(48)(49)(50). Specific receptors for most of these hormones and factors are present on the membranes of placental cells.…”
Section: A the Production Of Placental Hormones In Pregnancymentioning
confidence: 99%